Maintenance Therapy in First-Line Gastric and Gastroesophageal Junction Adenocarcinoma: A Retrospective Analysis - Walden, Daniel; Sonbol, Mohamad Bassam; Buckner Petty, Skye; Yoon, Harry H.; Borad, Mitesh; Bekaii-Saab, Tanios S.; Ahn, Daniel H. (Frontiers in Oncology, 2021)
Background Fluoropyrimidine with platinum-based chemotherapy has become the standard of care for advanced gastric and gastroesophageal (GEJ) cancer. Trials in colon cancer show that induction chemotherapy followed by maintenance chemotherapy is an efficacious strategy to maximize clinical response while minimizing toxicity. The current retrospective study aims to evaluate the efficacy and tolerability of maintenance versus continuous treatment in advanced GEJ malignancy. Methods A retrospective analysis of patients with metastatic gastric/GEJ adenocarcinoma treated with fluoropyrimidine and platinum chemotherapy between 2007-2017 was performed. Patients who achieved at least stable disease after initial induction treatment were included. After 16 weeks of induction chemotherapy, patients were categorized into the continuous group if induction chemotherapy was continued and the maintenance group if chemotherapy was switched to maintenance fluoropyrimidine monotherapy or observed off treatment. Endpoints were progression-free survival (PFS), overall survival (OS), and toxicities. Results In total, 90 patients met the criteria, 48 received continuous therapy, and 42 received maintenance. Baseline characteristics were comparable. No difference in PFS (9.9 vs 8.4 months p = .28) or in OS (16.1 vs 21.3 months p = .75) was observed, including after controlling for the best response on induction therapy and other variables. In patients on continuous induction therapy, there was a higher prevalence of grade three neuropathy (42.6% vs 9.8% p = .001) and neutropenic fever (13% vs 0% p =.03). Conclusions Maintenance therapy following induction fluoropyrimidine and platinum-based therapy is associated with an improved toxicity profile and appears to have comparable efficacy to continuous treatment in metastatic gastric/GEJ cancer.